Alpha-F-Convex Contraction Mappings in b-Metric Space and a Related Fixed Point Theorem. (7th October 2021) - Geleta, Kitila Wirtu; Tola, Kidane Koyas; Teweldemedhin, Solomon Gebregiorgis
Abstract : In this paper, we establish fixed point theorems for α -F -convex contraction mappings in b -metric space and prove the existence and uniqueness of fixed points for such mappings. Our result extends and generalizes comparable results in the existing literature. Finally, we provide an example in support of our main finding.